2021
DOI: 10.1021/acsenergylett.1c01049
|View full text |Cite
|
Sign up to set email alerts
|

Charge Recycling Mechanism Through a Triplet Charge-Transfer State in Ternary-Blend Organic Solar Cells Containing a Nonfullerene Acceptor

Abstract: We investigated the side-group and backbone-extension effects of a push−pull conjugated polymer (CP) on the charge-generation mechanism in ternary-blend organic solar cells (OSCs) containing PC 71 BM and a nonfullerene acceptor (NFA, ITIC). Transient absorption spectroscopy results revealed that the CP extension increased the hole-transfer efficiency from ITIC to the CPs, inducing the formation of triplet (T 1 ) excitons by nongeminate recombination (via triplet charge-transfer states, 3 CT) because of the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
(91 reference statements)
3
13
0
Order By: Relevance
“…The formation dynamics of the LPs at the interface within the BHJ film (disordered domains) is faster than that of the DPs in the ordered domains that are away from the interfaces . We confirmed that the formation dynamics of the PIA peak at approximately 960 nm were faster than those of the PIA peak at approximately 700 nm in the TAS of CP/PC 71 BM BHJ blend films . The SE signal quenching dynamics at approximately 700 nm in the TAS of CP thin films was clearly observed due to the inter-PP formation (Figures S8–S10).…”
Section: Results and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The formation dynamics of the LPs at the interface within the BHJ film (disordered domains) is faster than that of the DPs in the ordered domains that are away from the interfaces . We confirmed that the formation dynamics of the PIA peak at approximately 960 nm were faster than those of the PIA peak at approximately 700 nm in the TAS of CP/PC 71 BM BHJ blend films . The SE signal quenching dynamics at approximately 700 nm in the TAS of CP thin films was clearly observed due to the inter-PP formation (Figures S8–S10).…”
Section: Results and Discussionsupporting
confidence: 64%
“…We assigned the PIA peaks in the dotted–dashed circles at approximately 1200 nm in Figure to the S 1 excitons of the CP corresponding to each panel. In our previous report, the OD value of the PIA peak at approximately 1200 nm significantly decreased (the peak shape totally collapsed) in the TAS of the PBT-OTT/PC 71 BM bulk-heterojunction (BHJ) blend film compared to that in the TAS of the PBT-OTT neat film owing to PBT-OTT S 1 quenching by PC 71 BM . In contrast, the PIA peaks at approximately 700 and 900 nm in the TAS of the PBT-OTT/PC 71 BM blend film were considerably larger and more distinct than those for the PBT-OTT neat film; thus, we assigned these peaks to the positive polaron states in the PBT-OTT domains.…”
Section: Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the case of the 680 nm pump (the interchain packing-dominant domains are more excited than the intrachain ordering-dominant domains), the formation dynamics of CT states from P4TNTz-2F to PC 71 BM (the k 1 pathway at the top of Figure ) is slightly faster (3.25 ps) in blend #2 than in blend #1 (3.32 ps) (Table ). Generally, the CT states form well more in the amorphous BHJ blends than in the highly crystalline BHJ blends because of the more efficient formation of interfaces between the donors and acceptors in the amorphous BHJ blends than in the highly crystalline BHJ blends. , However, the target analysis results of Figure a and Table show the opposite tendency. This implies that the highly crystalline P4TNTz-2F NWs with the 6 nm widths in blend #2 would promote more efficiently the CT from P4TNTz-2F to PC 71 BM than the relatively low crystalline P4TNTz-2F NWs with the 14 nm widths in blend #1; the large surface area of the narrow P4TNTz-2F NW structure allows the efficient formation of the interfaces within the BHJ blend.…”
Section: Resultsmentioning
confidence: 94%
“…A trade-off between radiative energy loss, energy loss associated with CT state formation, and non-radiative energy loss has been carefully analyzed to design efficient NFA-based OPVs. The extensions on the donor-conjugated polymer have enhanced the efficiency of hole transfer from NFA to the polymer in a ternary blend organic solar cell . Transient absorption spectroscopy revealed the free charge carrier recycling as a result of suppression of triplet exciton formation from 3 CT states by PC 71 BM.…”
mentioning
confidence: 99%